The Catholic ethic in American society: an exploration of values - Tropman, John E. (The Jossey-Bass nonprofit sector series, 1995)
Based on years of scholarly research, the Catholic Ethic in American Society reveals a Catholic ethic that parallels the more well-known Protestant ethic. Tropman presents an innovative analysis of the deeply ingrained attitudes Americans have about money and work and their view of people who have neither. In this book, Tropman offers a fresh perspective on the Protestant "achievement" ethic by contrasting it with the newly identified Catholic "sharing" ethic